(untitled) (World Bulletin of Social Sciences, 2022)
The shadow economy is a concern in every state. It should be acknowledged that overcoming the shadow economy is one of the most pressing issues facing state regulation and administration. The shadow economy is defined as economic activity that is intentionally concealed from the government and public. This activity occurs outside of the purview of governmental regulation and accountability. This article discusses the shadow economy, its challenges, and its importance in emerging countries’ economies